Alopecia totalis in a patient with Crohn's disease and its treatment with azathioprine. - Goddard, C. J. (BMJ Group, 1989)
A patient with Crohn's disease and alopecia totalis is described. Despite relative inactivity of the Crohn's disease, treatment with azathioprine was commenced. This led to complete regrowth of hair which was lost when the drug was discontinued. Re-institution of azathioprine restored hair to normal again and the patient has since declined to try stopping the drug despite the knowledge of potential side effects.